2020
DOI: 10.1186/s12889-020-09312-1
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare retention and clinical outcomes among adolescents living with HIV after transition from pediatric to adult care: a systematic review

Abstract: Background: Adolescents living with HIV (ALWH) who transition from pediatric to adult care face several challenges that increase their risk of experiencing treatment interruptions and being lost to HIV care with resultant increased morbidity and mortality. To date, few studies have examined their outcomes post-healthcare transition (HCT), precluding the development and dissemination of evidence-based interventions aimed at retaining ALWH in HIV care both during and after HCT. We conducted a systematic review t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…In a study in United Kingdom, among young adults with perinatally acquired HIV infection that assessed the clinical outcomes post transition to adult services, 86% of these youths were retained in HIV care [ 27 ]. In a systematic review by Ritchwood et al [ 28 ] to examine retention in HIV care, it indicated that more than 70% of such adolescents who were infected with HIV perinatally were retained in care 1–2 years post-Health Care Transition. Such youths are better retained in care because of the special attention they receive during their paediatric HIV care, and the intense preparations for transitions into adult care [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study in United Kingdom, among young adults with perinatally acquired HIV infection that assessed the clinical outcomes post transition to adult services, 86% of these youths were retained in HIV care [ 27 ]. In a systematic review by Ritchwood et al [ 28 ] to examine retention in HIV care, it indicated that more than 70% of such adolescents who were infected with HIV perinatally were retained in care 1–2 years post-Health Care Transition. Such youths are better retained in care because of the special attention they receive during their paediatric HIV care, and the intense preparations for transitions into adult care [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These adolescents and young adults have been found to have a special patient-provider relationship that is constituted by a strong bond in between since the provider understands the patient in details [ 29 ]. There is an element of adaptation to the clinic environment, boosted by the individual experience [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…While CAWH‐focused HIV services may offer individualized behavioural and social support, transitioning into adult care often negatively affects older youth as they “age out” of more child‐friendly paediatric health systems into larger clinics that lack such support services. This transition period can be a time of increased risks of poor adherence and viral outcomes [8].…”
mentioning
confidence: 99%
“…A key strength of the intervention was its comprehensive nature (i.e., it was designed to address a broad spectrum of unmet social and health needs) and individualized design (i.e., it sought to respond to each adolescent's needs, tailoring the intensity of support offered to each participant). Research has highlighted the limited efficacy of a "one size fits all" approach for community-based interventions [8,44,45], in part because subgroups at highest risk may need extra support [46,47]. In this intervention, entry-level health workers filled gaps in care, provided linkages, liaised with providers, and literally accompanied adolescents as they transitioned to adult care.…”
Section: Discussionmentioning
confidence: 99%